University students´ beliefs about responsibility: implications for social intervention - García Hernández, Fernando Rubén (2022)
We investigate how the beliefs about the prototypes of responsible person and irresponsible person of future social and healthcare professionals may impact their attitudes and behavior regarding the social inclusion of vulnerable subjects. We asked 520 university students to spontaneously cite four adjectives describing the prototypes and then to order them according to each prototype. The responsible person was described using the terms constant, applied, careful, focused, and hardworking. The irresponsible person was described by highlighting the terms lazy, reckless, and volatile. The prototypes tend to be described using pairs of opposite terms: constant-inconstant, careful-careless, organized-disorganized, mature-immature, punctual-unpunctual, prudent-imprudent, and conscientious-mindless. We conclude that perseverance, individual freedom, and performance appear as three inclusion-exclusion criteria related to beliefs about responsibility and irresponsibility. We state that these beliefs are congruent with professional attitudes that seek socio-occupational integration rather than social inclusion and personal development from diversity.